Christians at the heart of Islamic rule : church life and scholarship in ʻAbbasid Iraq - Woodbrooke-Mingana Symposium on Arab Christianity and Islam 2001 : Woodbrooke Quaker Study Centre); Thomas, David (David Richard), 1948- (Leiden ; Boston : Brill, 2003)
The chapters in this volume, which come from the Fourth Woodbrooke-Mingana Symposium, cover aspects of Christian life in and around Baghdad in the early centuries of 'Abbasid rule. The authors explore both broad themes, such as the place of monasteries in Muslim cultural life, accusations of Islam as crypto-idolatry, and Muslim responses to Christian apologetic arguments, and also specific topics, such as a Nestorian's explanation of the Incarnation, a Jacobite's purpose in composing his guide to moral improvement, and the development of Christian legends about the caliph al-Ma'mun. The volume illustrates the vigour of Iraqi Christian life in 'Abbasid times, and helps show that relations between Christians and Muslims, although strained at times, were often beneficial to followers of both faiths.
Muslims as crypto-idolaters: a theme in the Christian portrayal of Islam in the Near East / Barbara Roggema -- Monasteries through Muslim Eyes: the Diyarat Books / Hilary Kilpatrick -- Habib ibn Khidma Abu Ra'ita al-Takriti's 'The Refutation of the Melkites concerning the Union [of the Divinity and Humanity in Christ]' (III) / Sandra Toenies Keating -- 'Ammar al-Basri on the Incarnation / Mark Beaumont -- The Christian al-Ma'mun Tradition / Mark N. Swanson -- Stuccowork at the Monastery of the Syrians in the Wadi Natrun: Iraqi-Egyptian Artistic Contact in the 'Abbasid Period / Lucy-Anne Hunt -- The 'Philosophical Life' in Tenth Century Baghdad: the Contribution of Yahya Ibn 'Adi's Kitab tahdhib al-akhlaq / Sidney Griffith -- Yahya Ibn 'Adi and the Theory of Iktisab / Emilio Platti -- Language and thought in Kitab al-majdal, bab 2, fasl 1, al-Dhurwa / Bo Holmberg -- The two recensions of the Prologue to John in Ibn al-Tayyib's Commentary on the Gospels / Julian Faultless -- The Ultimate Proof-Text: The Interpretation of John 20.17 in Muslim-Christian Dialogue (second/eighth-eight/fourteenth centuries) / Martin Accad -- A Medieval Islamic Polemic against Certain Practices and Doctrines of the East Syrian Church: Introduction, Excerpts and Commentary / Gabriel Said Reynolds -- Early Muslim Responses to Christianity / David Thomas.
Includes bibliographical references (pages 255-266) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Iraq -- Church history -- Middle Ages, 600-1500 -- Congresses; Christianity and other religions -- Islam -- Congresses; Islam -- Relations -- Christianity -- Congresses; Christianisme -- Relations -- Islam -- Congrès.; Islam -- Relations -- Christianisme -- Congrès.; Irak -- Histoire religieuse -- 600-1500 (Moyen Âge) -- Congrès.; RELIGION -- Christianity -- History; Christianity; Interfaith relations; Islam; Iraq; Islam; Interreligiöser Dialog; Christentum; Abbasidenreich; Irak; Christenen; Islam; Abbasiden; Birmingham <2001>; 600-1500; Teologi -- Teologi; Church history; Conference papers and proceedings